1998
DOI: 10.1590/s0074-02761998000700040
|View full text |Cite
|
Sign up to set email alerts
|

Possible hybridization of Brazilian planorbid snails and its importance in population dynamics

Abstract: This study focuses on the possibility of experimental hybridization among host snail species forIntraspecific and interspecific crossbreedings among host species have been described in the literature since the 1950s. Paraense (1955) and Paraense and Deslandes (1955) performed experiments based on intra-and interspecific crossbreeding. The former, intraspecific crossbreeding, aimed to establish these species' reproductive preferences, while the latter focused on the possibility of interspecific crossbreeding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Note that VE6b and VE13a are also genetically closer to BR1 individuals than to other Venezuelan individuals, when using microsatellite (nuclear) markers (Mavarez et al, 2002b). A possible explanation to such a nuclear-mitochondrial conflict involves interspecific (or inter-clade) mitochondrial gene flow via hybridisation, which is common in animals (Barton and Hewitt, 1985), and has been documented in Biomphalaria (Mello-Silva et al, 1998;Kristensen et al, 1999). However it is also possible that the 16S gene tree is poorly resolved, due to a lower evolutionary rate.…”
Section: The Northern Cladementioning
confidence: 99%
“…Note that VE6b and VE13a are also genetically closer to BR1 individuals than to other Venezuelan individuals, when using microsatellite (nuclear) markers (Mavarez et al, 2002b). A possible explanation to such a nuclear-mitochondrial conflict involves interspecific (or inter-clade) mitochondrial gene flow via hybridisation, which is common in animals (Barton and Hewitt, 1985), and has been documented in Biomphalaria (Mello-Silva et al, 1998;Kristensen et al, 1999). However it is also possible that the 16S gene tree is poorly resolved, due to a lower evolutionary rate.…”
Section: The Northern Cladementioning
confidence: 99%
“…The identification errors found between B. glabrata and B. tenagophila indicate that the chemical phenotypes of the two species are the most similar. This may be related to the morphological and biological similarities of these two species, and their possible potential for hybridization (9,23). However, Vidigal et al (24) found that B. glabrata and B. tenagophila belonged to distinct clades in a phylogenetic analysis of the ITS2 molecular marker, which indicates that there is a considerable genetic distance between the two species.…”
Section: Discussionmentioning
confidence: 99%
“…Crosses between Biomphalaria species that produced fertile hybrids have been reported. Examples include crosses between B. alexandrina and B. glabrata (Barbosa et al 1956): B. straminea and B. peregrine, B. tenagophila and B. peregrina (Barbosa et al 1958) and B. glabrata and B. tenagophila (Mello-Silva et al 1998). Barbosa (1964) (66) 21 (42) 43 (86) 10 ( this process of competitive exclusion were mixed forms found, possibly as a result of crosses between these species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study confirms that these two species produce hybrids. Mello-Silva et al (1998) commented that the results of fertility and fecundity tests of fertile hybrids revealed that the F2 generation was not as efficient as the F1, involving the formation of normal, vigorous and fertile F1 generation hybrids, but a weak F2 generation with the presence of some sterile individuals. However, further studies are necessary to better understand the biology of these hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation